An efficient enzymatic preparation of 20-pregnane succinates: chemoenzymatic synthesis of 20β-hemisuccinyloxy-5αH-pregnan-3-one - Monsalve, Leandro Nicolas (2008)
Lipase-catalyzed transesterification of the 20 hydroxyl group in a series of pregnanes afforded novel 20-ethyl succinates that are not possible to prepare following the traditional synthetic methods. The reaction is stereoselective. The enzyme reacts selectively with the 20β epimers therefore only the 20β-succinyloxy derivatives are obtained. These compounds are obtained in variable yield, depending on the substitution in the ring A. The enzymatic approach allowed, for the first time, the synthesis of 20β-hemisuccinyloxy-5αH-pregnan-3-one, novel compound useful as a precursor of steroid-protein conjugates. © 2007 Elsevier Ltd. All rights reserved.